Validity of E-LKPD Based on Problem Based Learning Using Live Worksheets to Improve Creative Thinking Skills on Renewable Energy Material - Selfi Selfi; Dea Stivani Suherman; Asrizal Asrizal; Fauziah Ulmi (Department of Physics Universitas Negeri Padang, 2026)
This study aims to develop a Problem-Based Learning (PBL)-based Electronic Student Worksheet (E-LKPD) using Live Worksheets on renewable energy topics and to determine its validity. The research uses a Research and Development (R&D) approach with the 4D model (define, design, develop). Data were collected through a validation questionnaire assessed by three experts using the Aiken’s V index. The results show an average validity score of 0.93, categorized as very valid, indicating that the product is feasible for use in physics learning. The integration of Live Worksheets also provides interactive digital support that has the potential to enhance students’ creative thinking skills. However, this study is limited to the validity stage; therefore, further research is needed to examine its practicality and effectiveness in classroom implementation.